Diversity of Soil Macro Insect in Alas Purwo National Park, Banyuwangi, East Java, Indonesia - Astri Dwi Wulandari; Tutik Indrawati; Fitrahyanti Fiqqi Maghfirah; Eka Kartika Arum Puspita Sari; Shifa Fauziyah; Rosmanida Rosmanida (Journal of Tropical Biodiversity and Biotechnology, 2018)
Indonesia is the second largest mega biodiversity of the world. One of the forest resources are soil insects. Soil insects improved the soil physical properties, added organic material content, and used as bio-indicator of environmental conditions of conservation areas, forests, or mountains. The aim of this research was to get information about the diversity, dominance, and similarity index of soil macro insect in Alas Purwo National Park, Banyuwangi, East Java, Indonesia in 2017. Locations were selected based on purposive random sampling considering 2 habitat types; coastal forest path and tropical rain forest path. The method of this research was used pitfall trap. Insects were identified at Laboratory of Ecology, Biology Department, Faculty of Science and Technology, Airlangga University, Surabaya. The results showed that the diversity index of soil insects in the coastal forest path was 1.611 and in path of tropical rain forest was 0.855. It means that the diversity of soil macro insect in coastal forest path were medium and in path of tropical rain forest was low. The Dominancy index of coastal forest path was 0.334 and in path of tropical rain forest was 0.433. It means that the community was stable, there was no species domination. The similarity index of soil insects in both paths have a 58.8%, was a unity of the same community.